The Joneses in Japan: Income comparisons and financial satisfaction - Andrew E. Clark; Claudia Senik; Katsunori Yamada (Osaka University, Institute of Social and Economic Research (ISER), 2013)
This paper uses Japanese data which includes measures of self-declared satisfaction, reference-group income, and the direction and intensity of income comparisons. Relative to Europeans, the Japanese compare more to friends and less to colleagues, and compare their incomes more. The relationship between satisfaction and others' income is negative, and more negative for those who report greater income comparison intensity. A self-reported measure of others' income does better than cell-mean income in explaining satisfaction, and would arguably make a useful addition to many existing surveys.
Keywords: D31; D63; I3; J31; 330; Income Comparisons; Reference-Group Income; Reference Groups; Satisfaction; Zufriedenheit; Haushaltseinkommen; Vergleich; Zeitreihenanalyse; Japan